Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\frac{5.2^{30}.3^{18}-2^2.3^{20}.2^{27}}{5.2^9.2^{19}.3^{19}-7.2^{29}.3^{18}}=\frac{5.2^{30}.3^{18}-2^{29}.3^{20}}{5.2^{28}.3^{19}-7.2^{29}.3^{18}}=\frac{2^{28}.\left(5.2^2.3^{18}-2.3^{20}\right)}{2^{28}.\left(5.3^{19}-7.2.3^{18}\right)}=\frac{3^{18}.\left(5.2^2-2.3^2\right)}{3^{18}.\left(5.3-7.2\right)}=\frac{5.2^2-2.3^2}{5.3-7.2}=\frac{2}{1}=2\)
\(7^2.49^3.7^7=7^2.\left(7^2\right)^3.7^7=7^2.7^6.7^7=7^{15}\)
\(3^5.9^4.27^2.81=3^5.\left(3^2\right)^4.\left(3^3\right)^2.3^4=3^5.3^8.3^6.3^4=3^{23}\)
a) \(7^2.49^3.7^7=7^2.7^6.7^7=7^{15}\)
b) \(3^5.9^4.27^2.81=3^5.3^8.3^6.3^4=3^{23}\)
không biết đâu
Dương Dương Hà thì đừng trả lời